(untitled) (Medico Legal Update, 2020)
In the present study, the DPPH scavenging activity from the primary methods to estimation the antioxidants activity in the body by an inverse relation between them. So, the levels of DPPH scavenging activity is reduced in the patient with HPV16 genotype chronic cervicitis (G3= 43.01±2.74 in the serum, G3= 9.73±1.53 in the mucus) and without (G2= 47.22±4.50 in the serum, G2= 15.51±1.41 in the mucus)compared with healthy women (G1= 64.79±4.87 in the serum, G1= 21.24±3.62 in the mucus), this is a return to lowering antioxidants in the patients compared with healthy women. The deterioration in the antioxidants levels can cause cancer in the future or delay the response of the medication to inflammation.